Community Food Rescue and Food Banks in Peru: Local experiences to improve food nutrition in Lima peri-urban suburbs - Pradel, W.; Santandreu, A.; Fuentes, A.; Tueroconza, E.; Ninahuamán, J.; López, D. (2025)
This report documents community-led food rescue and food bank initiatives in Lima, Peru, focusing on REDOPA’s model of recovering surplus food from farms and wholesale markets. Led primarily by women from community kitchens, these initiatives have reduced waste, improved access to nutritious foods, and strengthened local food systems. Despite regulatory challenges, food rescue efforts demonstrate scalable solutions for addressing food insecurity and environmental sustainability. The report highlights the importance of institutional support, clear policy frameworks, and community autonomy in building resilient food systems.